Estimation of Genetic Variance and Heritability of F2 Populations of Corn Plants in Dry Land - I Wayan Sudika; I Wayan Sutresna; Dwi Ratna Anugrahwati (Postgraduate, University of Mataram, 2022)
This study was aimed to determine the genetic variance of several F2 population traits of maize, broad heritability values and phenotypic correlations between yields and other quantitative traits. The method used is the experimental method. The experiment was designed in a randomized block design, with 6 replications. The number of treatments was 4 populations, namely population F2, Sinta Unram, hybrid NK212 and NK7328. Each population was planted in 4 rows, each consisted of 40 plants. The observed characteristics included plant height, leaf number per plant, leaf angle, ear length, ear diameter, weight of dry ear harvested per plant and yield (dry seed weight per plant). The data were analyzed by simple statistical analysis and analysis of variance at the 5 percent level of significance. The results showed that the genetic variance of plant height, leaf angle, and dry cob weight at harvest per plant population of F2 was higher than that of Sinta Unram's genetic diversity with relatively wide genetic diversity. The genetic variance of leaf number per plant, ear length and ear diameter were also higher than that of Sinta Unram; but the genetic diversity is quite narrow. The genetic diversity of the F2 population's traits is the same as that of Sinta Unram with a broad category. The heritability value of broad meaning classified as high (> 50 %) was obtained on plant height, leave number per plant, ear length, ear diameter, weight of dry ear harvested per plant and yield; while the leaf angle is classified as moderate. Harvested dry cobs weight per plant showed strong phenotypic correlation with yield (0.827); while other properties are classified as very weak to moderate. Improving the yield of the F2 population can be done by indirect mass selection using the weight of harvested dry cobs per plant as the selected trait